Boron nitride powder and resin composition
By controlling the pore structure of boron nitride powder, the problem of insufficient thermal conductivity of existing boron nitride powders is solved, and boron nitride powder with high density and high thermal conductivity is achieved, thereby improving the performance of heat dissipation materials.
Patent Information
- Application Number
- CN202380062838.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-30
- Filing Date
- 2023-08-22
- Publication Date
- 2025-04-08
AI Technical Summary
When used in thermally conductive materials, the thermal conductivity is insufficient and the density is not high, which affects the heat dissipation performance.
By controlling the pore structure of the boron nitride powder, the slope of the differential pore volume curve within the range of the pore radius of 1.2 μm is ensured to be less than 0.8, thereby reducing the void volume inside the particles and increasing the density of the boron nitride powder.
The thermal conductivity and density of boron nitride powder are improved, so that when used in mixed with resin, the thermal conductivity and performance of the heat dissipation material can be significantly improved.
Smart Images

Figure CN119790016A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to boron nitride powder and a resin composition. Background Art
[0002] Boron nitride has lubricity, high thermal conductivity, and insulation properties, and is used in a variety of applications, including solid lubricants, mold release materials, cosmetic raw materials, heat dissipation materials, and heat-resistant insulating sintered bodies.
[0003] For example, Patent Document 1 discloses a hexagonal boron nitride powder, which is characterized in that it can impart high thermal conductivity and high insulation resistance to a resin composition obtained by filling it with a resin, and comprises aggregated particles formed of primary particles of hexagonal boron nitride, and has a BET specific surface area of 0.7 to 1.3 m 2 / g, and the oil absorption measured based on JIS K 5101-13-1 is 80 g / 100 g or less.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-160134 Summary of the invention
[0007] Problems to be solved by the invention
[0008] The main object of the present invention is to provide novel boron nitride powder.
[0009] Means for solving problems
[0010] The present invention provides the following [1] to [5] in some aspects.
[0011] [1] A boron nitride powder comprising boron nitride particles having pores, wherein in a curve of differential pore volume relative to pore radius measured by a mercury porosimeter, when a point where the differential pore volume curve rises and a point where the differential pore volume reaches a maximum value are connected by a straight line within a range of pore radius of 1.2 μm or less, the slope of the straight line is 0.8 or less.
[0012] [2] The boron nitride powder according to [1], wherein the cumulative pore volume within the range of pore radius of 1.2 μm or less is 0.2 ml / g or less.
[0013] [3] The boron nitride powder according to [1] or [2], wherein the maximum value is 0.4 ml / g or less.
[0014] [4] The boron nitride powder according to any one of [1] to [3], wherein the maximum value is 0.1 ml / g or more.
[0015] [5] A resin composition comprising a resin and the boron nitride powder according to any one of [1] to [4].
[0016] Effects of the Invention
[0017] According to one aspect of the present invention, a novel boron nitride powder can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] [ Figure 1 ] is a curve chart of the X-ray diffraction measurement results of the boron nitride powder obtained in Example 1.
[0019] [ Figure 2 ] is the pore size distribution of the boron nitride powder obtained in Example 1.
[0020] [ Figure 3 ] is the pore size distribution of the boron nitride powder obtained in Example 2.
[0021] [ Figure 4 ] is the pore size distribution of the boron nitride powder obtained in Example 3.
[0022] [ Figure 5 ] is the pore size distribution of the boron nitride powder obtained in Comparative Example 1. DETAILED DESCRIPTION
[0023] Hereinafter, embodiments of the present invention will be described in detail.
[0024] The boron nitride powder according to the present embodiment includes boron nitride particles having pores, and may be an aggregate of a plurality of boron nitride particles (boron nitride particles having pores).
[0025] Each of the plurality of boron nitride particles is composed of, for example, a plurality of boron nitride flakes. The pores of the boron nitride particles may be formed between the plurality of boron nitride flakes. The boron nitride flakes are formed of boron nitride and may have, for example, a scale-like shape.
[0026] The plurality of boron nitride sheets may be in physical contact or may be chemically bonded to each other. Whether the plurality of boron nitride sheets are chemically bonded to each other can be confirmed by not observing the boundary between the boron nitride sheets at the bonded portion of the boron nitride sheets using SEM.
[0027] The boron nitride particles may include a cross section having a region where a plurality of boron nitride sheets are stacked. The stacking of a plurality of boron nitride sheets can be confirmed by observing the cross section of the boron nitride particles using SEM and by the plurality of boron nitride sheets being arranged side by side in the thickness direction of the boron nitride sheets.
[0028] The average thickness of the boron nitride sheet can be 0.5 μm or more, 1 μm or more, or 1.5 μm or more, and can be 5 μm or less. The average length of the length direction of the boron nitride sheet can be, for example, 1 μm or more, and can be 10 μm or less. The average thickness and the average length in the length direction of the boron nitride sheet are defined as: the SEM image obtained by observing the cross section of the boron nitride particles using SEM at a magnification of 1000 times is imported into the image analysis software (for example, "Mac-view" manufactured by Mountech Co., Ltd.), and the average value of the thickness and the length in the length direction of 40 boron nitride sheets measured in the SEM image.
[0029] The boron nitride particles may consist essentially of only boron nitride. That the boron nitride particles consist essentially of only boron nitride can be confirmed by detecting only a peak derived from boron nitride in X-ray diffraction measurement.
[0030] In the case of boron nitride powder, a curve of differential pore volume relative to pore radius measured using a mercury porosimeter (horizontal axis: pore radius, vertical axis: differential pore volume) has a maximum value (peak) within the range of pore radius of 1.2 μm or less. This maximum value is a maximum value in which the slope of a straight line is 0.8 or less when a point where the differential pore volume curve rises and a point where the differential pore volume reaches a maximum value are connected by a straight line.
[0031] More specifically, in the curve of differential pore volume relative to pore radius, within the range of pore radius below 1.2 μm, the differential pore volume at the point where the curve of differential pore volume rises is set to V1 (ml / g), the pore radius when the differential pore volume is V1 is set to R1 (μm), the differential pore volume at the point where the differential pore volume reaches a maximum value is set to V2 (ml / g), the pore radius when the differential pore volume reaches a maximum value V2 is set to R2 (μm), and the slope a represented by the following formula (1) is below 0.8.
[0032] a=(V2-V1) / (R2-R1) · · · (1)
[0033] By making the boron nitride powder have a peak in which the slope of the straight line (the slope a represented by the above formula (1)) is 0.8 or less in the curve of the differential pore volume relative to the pore radius, the number of pores with small pore radius in each boron nitride particle in the boron nitride powder is small, and thus the volume of the voids existing inside the particle is also reduced. Therefore, the boron nitride powder becomes dense boron nitride particles, and such a boron nitride powder, for example, when mixed with a resin and used as a thermal conductive material (for example, a heat dissipation material), can exhibit a higher thermal conductivity than conventional boron nitride powder.
[0034] As for the curve of differential pore volume relative to pore radius, a mercury porosimeter is used and the method is based on mercury injection according to JIS R1655: 2003. The curve of differential pore volume is obtained by the following steps. Specifically, first, the differential pore volume relative to pressure is measured in the range of 0.40 to 60000 psia using a mercury porosimeter. At this time, in a logarithmic curve graph with the logarithm of pressure as the horizontal axis and the differential pore volume as the vertical axis, the value of the pressure for measuring the differential pore volume is set to 130 points at equal intervals on the horizontal axis. Then, the pressure is converted into the pore radius, and then the measured differential pore volume relative to the logarithm of the converted pore radius is plotted, and the plot points are connected with a straight line to obtain a curve of differential pore volume relative to the pore radius.
[0035] The point where the differential pore volume curve rises is defined as the point where the differential pore volume becomes 0.02 ml / g. That is, the differential pore volume V1 in formula (1) is 0.02 ml / g, and the pore radius R1 is the pore radius when the differential pore volume becomes 0.02 ml / g. In the range where the differential pore volume is less than 0.02 ml / g, the influence of noise in the measurement is large, so the point where the differential pore volume becomes 0.02 ml / g is defined as the point where the differential pore volume curve rises. It should be noted that in the range where the pore radius is less than 1.2 μm, when there are multiple points where the differential pore volume becomes 0.02 ml / g, the point with the smallest pore radius among the multiple points is defined as the point where the differential pore volume curve rises.
[0036] The maximum value (peak) of the differential pore volume is defined as the measurement point where the change in the differential pore volume with respect to the pore radius changes from positive to negative with the increase in the pore radius in the curve of the differential pore volume. That is, among the measurement points of the differential pore volume, for the m-1th measurement point (pore radius: R m-1 (μm), differential pore volume: V m-1 (ml / g)), mth measurement point (pore radius: R m (μm), differential pore volume: V m (ml / g)), and the m+1th measurement point (pore radius: R m+1 (μm), differential pore volume: V m+1 (ml / g)), satisfying R m-1 <R m <R m+1 , and satisfy V m -V m-1 >0 and V m+1 -V m The mth measurement point where V < 0 is defined as the point where the differential pore volume becomes a maximum value. m+1=V m In the case of m+nth measurement point (pore radius: R m+n (μm), differential pore volume: V m+n (ml / g), n: 2 or more, and meets V m ≠V m+n The smallest integer that satisfies R m-1 <R m <R m+n , and satisfy V m -V m-1 >0 and V m+n -V m <0 is defined as the point where the differential pore volume reaches a maximum value. It should be noted that, in the range of pore radius of 1.2 μm or less, when there are multiple points where the differential pore volume reaches a maximum value, the point with the smallest pore radius among the multiple points is defined as the point where the differential pore volume reaches a maximum value.
[0037] The pore radius R1 may be 0.01 μm or more, 0.02 μm or more, 0.04 μm or more, 0.05 μm or more, or 0.06 μm or less, or 0.3 μm or less, 0.2 μm or less, 0.15 μm or less, 0.13 μm or less, 0.12 μm or less, or 0.11 μm or less.
[0038] The maximum value V2 can be less than 0.4 ml / g, less than 0.35 ml / g, less than 0.32 ml / g, less than 0.3 ml / g, less than 0.28 ml / g, or less than 0.26 ml / g, and can be greater than 0.1 ml / g, greater than 0.15 ml / g, greater than 0.19 ml / g, or greater than 0.2 ml / g.
[0039] The pore radius R2 may be 0.2 μm or more, 0.3 μm or more, 0.4 μm or more, 0.5 μm or more, or 0.6 μm or less, and 1.1 μm or less, 1 μm or less, 0.9 μm or less, 0.8 μm or less, or 0.7 μm or less.
[0040] The slope of the straight line (the slope a represented by the formula (1)) may be 0.7 or less, 0.6 or less, or 0.5 or less, and may be 0.1 or more, 0.2 or more, 0.3 or more, or 0.35 or more.
[0041] The curve of the differential pore volume relative to the pore radius may also be a curve in which the differential pore volume changes (decreases) gently within the range from the pore radius R2 at which the differential pore volume becomes a maximum value V2 to the pore radius 1.2 μm. Specifically, when the minimum value of the differential pore volume within the range from the pore radius R2 at which the differential pore volume becomes a maximum value V2 to the pore radius 1.2 μm is set to V3 (ml / g), and the pore radius at which the differential pore volume becomes a minimum value V3 is set to R3 (μm), the slope b=(V2-V3) / (R2-R3) of the straight line connecting the maximum value V2 and the minimum value V3 may be less than -0.01, less than -0.04, or less than -0.05, and may be greater than -0.5, greater than -0.4, greater than -0.3, greater than -0.2, or greater than -0.1.
[0042] The cumulative pore volume of the boron nitride powder within the range of pore radius of 1.2 μm or less measured by a mercury porosimeter can be 0.2 ml / g or less, 0.19 ml / g or less, or 0.18 ml / g or less. The cumulative pore volume within the range of pore radius of the boron nitride powder of 1.2 μm or less can be regarded as the total amount of voids in each boron nitride particle constituting the boron nitride powder, so the smaller the cumulative pore volume within the range of pore radius of 1.2 μm or less, the easier it is for the boron nitride particles to become dense particles. Therefore, when such boron nitride particles are mixed with a resin to make a heat dissipation material, even if the boron nitride particles are not crushed, the filling rate of the boron nitride particles becomes high, and a heat dissipation material with high thermal conductivity is easily obtained. The cumulative pore volume within the range of pore radius of 1.2 μm or less measured by a mercury porosimeter may be 0.1 ml / g or more, 0.12 ml / g or more, 0.14 ml / g or more, 0.15 ml / g or more, 0.16 ml / g or more, or 0.17 ml / g or more.
[0043] The boron nitride powder may have a cumulative pore volume within a range of pore radius of 500 μm or less measured by a mercury porosimeter of 1 ml / g or less, 0.95 ml / g or less, or 0.91 ml / g or less. The cumulative pore volume may be 0.7 ml / g or more, 0.8 ml / g or more, 0.85 ml / g or more, 0.88 ml / g or more, or 0.9 ml / g or more.
[0044] The bulk density of the boron nitride powder may be 0.7 g / ml or more, 0.72 g / ml or more, 0.74 g / ml or more, or 0.75 g / ml or less, and 0.9 g / ml or less, 0.8 g / ml or less, or 0.75 g / ml or less.
[0045] The average particle size of the boron nitride powder can be, for example, 10 μm or more, 20 μm or more, or 30 μm or more, or 100 μm or less, 80 μm or less, or 60 μm or less. The average particle size of the boron nitride powder refers to the particle size (D50) at which the volume cumulative particle size distribution becomes 50%, and can be measured by laser diffraction scattering method.
[0046] The BET specific surface area of the boron nitride powder can be measured by the BET multipoint method using nitrogen gas in accordance with JIS Z 8830:2013. The BET specific surface area of the boron nitride powder can be 1 m 2 / g or more, 2m 2 / g or above, or 2.5m 2 / g or more, can be 5m 2 / g or less, 4m 2 / g or less, or 3.5m 2 / g or less.
[0047] The method for producing the above-mentioned boron nitride powder is described below. The above-mentioned boron nitride powder can be produced, for example, by a method having the following steps: a step of nitriding boron carbide particles while hot isostatic pressing (also called "Hot Isostatic Pressing") to obtain boron carbonitride particles (nitriding step); and a step of decarburizing the boron carbonitride particles to obtain a boron nitride powder containing boron nitride particles (decarburization step). That is, another embodiment of the present invention is a method for producing such a boron nitride powder. The method for producing the above-mentioned boron nitride particles is not limited to the above-mentioned method.
[0048] Boron carbide particles can be manufactured, for example, using known manufacturing methods. For example, the following method can be cited: after mixing boric acid and acetylene black, heat at 1800-2400°C for 1-10 hours in an inert gas atmosphere to obtain blocky boron carbide particles. The blocky boron carbide particles obtained by this method can be appropriately crushed, sieved, washed, impurity removed, and dried. The average particle size of the boron carbide particles can be, for example, 5 μm or more, 10 μm or more, or 15 μm or more, and can be 80 μm or less, 60 μm or less, or 40 μm or less. The average particle size of the boron carbide particles refers to the particle size (D50) at which the volume cumulative particle size distribution becomes 50%, which can be measured using a laser diffraction scattering method.
[0049] In the nitriding step, in an atmosphere that allows the nitriding reaction to proceed, the boron carbide particles are filled in a container and heated while being hot isostatically pressed, thereby nitriding the boron carbide particles to obtain boron carbonitride particles. The container may be, for example, a carbon crucible. Hot isostatic pressing may be performed using, for example, a hot isostatic pressing apparatus (e.g., manufactured by Kobe Steel).
[0050] The atmosphere in which the nitriding reaction in the nitriding step is performed may be a nitriding gas atmosphere for nitriding the boron carbide particles. The nitriding gas may be nitrogen, ammonia, or the like, and may be nitrogen from the viewpoint of easiness in nitriding the boron carbide particles and from the viewpoint of cost. The nitriding gas may be used alone or in combination of two or more, and the proportion of nitrogen in the nitriding gas may be 95% by volume or more, 99% by volume or more, or 99.9% by volume or more.
[0051] The pressure in the nitriding step may be 50 MPa or more, 70 MPa or more, or 100 MPa or more. The pressure in the nitriding step may be 200 MPa or less, or 150 MPa or less.
[0052] From the viewpoint of sufficiently nitriding the boron carbide particles, the heating temperature in the nitriding step may be 1600° C. or higher or 1700° C. or higher. The heating temperature in the nitriding step may be 2200° C. or lower or 2000° C. or lower.
[0053] From the viewpoint of fully nitriding the boron carbide particles, the time for pressurizing and heating in the nitriding step may be 30 minutes, 45 minutes or more, or 1 hour or more. The time for pressurizing and heating in the nitriding step may be 30 hours or less, 20 hours or less, or 10 hours or less.
[0054] In the decarburization step, the mixture containing the boron carbonitride particles obtained in the nitriding step and the boron source is heated in a state filled in a container, thereby decarburizing the boron carbonitride particles. The container may be, for example, a boron nitride crucible.
[0055] As the boron source, boric acid, boric oxide, or a mixture thereof can be cited. The mixture can also contain other additives used in the art as needed. The mixing ratio of the boron carbonitride particles and the boron source can be appropriately selected. When using boric acid or boric oxide as the boron source, the ratio of boric acid or boric oxide can be, for example, 50 or more parts by mass or 80 or more parts by mass, and can be 300 or less parts by mass or 200 or less parts by mass relative to 100 parts by mass of boron carbonitride.
[0056] The atmosphere in the decarburization step may be a normal pressure (atmospheric pressure) atmosphere or a pressurized atmosphere. The pressure in the decarburization step may be, for example, 0.5 MPa or less or 0.3 MPa or 0.01 MPa or more or 0.03 MPa or more.
[0057] In the decarburization process, for example, the temperature is first raised to a predetermined temperature (a temperature at which decarburization can be started), and then the temperature is further raised to a holding temperature at the predetermined temperature. The predetermined temperature (a temperature at which decarburization can be started) can be, for example, 1000° C. or higher, 1500° C. or lower, or 1200° C. or lower. The rate of raising the temperature from the predetermined temperature (a temperature at which decarburization can be started) to the holding temperature can be, for example, 5° C. / minute or lower, 4° C. / minute or lower, 3° C. / minute or lower, or 2° C. / minute or lower.
[0058] From the viewpoint of facilitating good particle growth, the holding temperature may be 1800° C. or higher or 2000° C. or higher. The holding temperature may be 2200° C. or lower or 2100° C. or lower.
[0059] From the viewpoint that particle growth is easy to occur well, the holding time at the holding temperature can be, for example, 0.5 hours or more, 1 hour or more, 3 hours or more, or 5 hours or more. The holding time at the holding temperature can be, for example, 40 hours or less, 30 hours or less, or 20 hours or less.
[0060] The boron nitride particles (boron nitride powder) obtained in this manner may be subjected to a step of classifying the boron nitride particles (boron nitride powder) so as to pass through a sieve to obtain a boron nitride powder having a desired particle size (classification step).
[0061] The boron nitride powder described above is suitable for use in heat dissipation components, for example. When the boron nitride powder is used in a heat dissipation component, it is used in the form of a resin composition obtained by mixing with a resin, for example. That is, another embodiment of the present invention is a resin composition containing a resin and the above-mentioned boron nitride powder.
[0062] From the viewpoint of improving the thermal conductivity of the resin composition and easily obtaining excellent heat dissipation performance, the content of the above-mentioned boron nitride powder can be 50% by volume or more, 55% by volume or more, 60% by volume or more, 65% by volume or more, or 70% by volume or more, based on the total volume of the resin composition. From the viewpoint of being able to suppress the generation of pores during molding and the reduction of insulation and mechanical strength, the content of the boron nitride powder can be 85% by volume or less, 80% by volume or less, or 75% by volume or less, based on the total volume of the resin composition.
[0063] Examples of the resin include epoxy resins, silicone resins, silicone rubbers, acrylic resins, phenolic resins, melamine resins, urea resins, unsaturated polyesters, fluororesins, polyimides, polyamide-imides, polyetherimides, polybutylene terephthalate, polyethylene terephthalate, polyphenylene ether, polyphenylene sulfide, wholly aromatic polyesters, polysulfones, liquid crystal polymers, polyethersulfones, polycarbonates, maleimide-modified resins, ABS (acrylonitrile-butadiene-styrene) resins, AAS (acrylonitrile-acrylic rubber·styrene) resins, and AES (acrylonitrile·ethylene·propylene·diene rubber-styrene) resins.
[0064] Based on the total volume of the resin composition, the resin content can be greater than 15 volume %, greater than 20 volume %, or greater than 25 volume %, and can be less than 50 volume %, less than 45 volume %, less than 40 volume %, less than 35 volume %, or less than 30 volume %.
[0065] The resin composition may further contain a curing agent for curing the resin. The curing agent is appropriately selected according to the type of the resin. For example, when the resin is an epoxy resin, phenol Novolac compounds, acid anhydrides, amino compounds, and imidazole compounds may be cited as curing agents. Relative to 100 parts by mass of the resin, the content of the curing agent may be, for example, 0.5 parts by mass or more or 1.0 parts by mass or less, and may be 15 parts by mass or less or 10 parts by mass or less.
[0066] The resin composition may further contain other components, such as a curing accelerator (curing catalyst), a coupling agent, a wetting and dispersing agent, a surface conditioner, and the like.
[0067] Examples of the curing accelerator (curing catalyst) include phosphorus-based curing accelerators such as tetraphenylphosphine tetraphenylborate and triphenyl phosphate, imidazole-based curing accelerators such as 2-phenyl-4,5-dihydroxymethylimidazole, and amine-based curing accelerators such as boron trifluoride monoethylamine.
[0068] Examples of the coupling agent include silane coupling agents, titanate coupling agents, and aluminate coupling agents, etc. Examples of the chemically bonded groups contained in these coupling agents include vinyl groups, epoxy groups, amino groups, methacrylic groups, and mercapto groups.
[0069] Examples of the wetting and dispersing agent include phosphate ester salts, carboxylic acid esters, polyesters, acrylic acid copolymers, and block copolymers.
[0070] Examples of the surface conditioner include acrylic surface conditioners, silicone surface conditioners, vinyl surface conditioners, and fluorine surface conditioners.
[0071] Example
[0072] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to the following examples.
[0073] (Example 1)
[0074] Boron carbide particles with an average particle size (D50) of 26 μm are filled in a carbon crucible, and a hot isostatic pressing device (manufactured by Kobe Steel) is used. In a nitrogen atmosphere, at 1800°C and 196 MPa, the boron carbide particles are heated and pressurized for 1.5 hours using the HIP method to nitride the boron carbide particles to obtain boron carbonitride particles (B4CN4). After 100 parts by mass of the obtained boron carbonitride particles are mixed with 150 parts by mass of boric acid (boric acid 60% by mass) using a Henschel mixer, the mixture is filled in a boron nitride crucible, and a resistance heating furnace is used to heat the mixture for 5 hours under normal pressure and nitrogen atmosphere while maintaining the temperature at 2000°C and 0.03 MPa, thereby obtaining coarse particles. After the coarse particles are crushed in a mortar for 10 minutes, they are classified using a nylon sieve with a mesh size of 175 μm. Thus, an aggregate (powder) of particles is obtained.
[0075] (Example 2)
[0076] A powder was obtained in the same manner as in Example 1 except that the amount of boric acid was changed to 100 parts by mass (boric acid 50% by mass).
[0077] (Example 3)
[0078] A powder was obtained in the same manner as in Example 1 except that the amount of boric acid was changed to 81.8 parts by mass (boric acid 45% by mass).
[0079] (Comparative Example 1)
[0080] Boron nitride powder was obtained in the same manner as in Example 1 except that the boron carbide particles were nitrided by heating and pressurizing at 2000° C. and 0.85 MPa for 25 hours in a nitrogen atmosphere using a resistance heating furnace to obtain boron carbonitride particles.
[0081] [X-ray diffraction measurement]
[0082] A portion of the powder obtained in each example was recovered and subjected to X-ray diffraction measurement using an X-ray diffractometer ("ULTIMA-IV" manufactured by Rigaku Corporation). The X-ray diffraction measurement results and the X-ray diffraction measurement results of the boron nitride powder obtained in Comparative Example 1 as a comparative object are shown in FIG. Figure 1 .according to Figure 1 It can be seen that only the peak derived from boron nitride was detected, and it was confirmed that boron nitride powder was obtained in each Example.
[0083] [Measurement of Differential Pore Volume of Boron Nitride Powder]
[0084] For the obtained boron nitride powder, a mercury porosimeter is used to measure the differential pore volume relative to the pore radius according to the following steps. The measuring device uses AutoPore IV9500 manufactured by Shimadzu Corporation, and the measuring cell uses a 5cc×1.1cc cell for powder. First, the differential pore volume relative to pressure is measured in the range of 0.40 to 60000 psia using a mercury porosimeter. At this time, in a logarithmic curve graph with the logarithm of pressure as the horizontal axis and the differential pore volume as the vertical axis, the value of the pressure for measuring the differential pore volume is set to 130 points at equal intervals on the horizontal axis. Then, the pressure is converted into the pore radius, and then the measured differential pore volume relative to the logarithm of the converted pore radius is plotted, and the plot points are connected with a straight line to obtain a curve of the differential pore volume relative to the pore radius. The curves of the differential pore volume with respect to the pore radius of the boron nitride powders obtained in Examples 1 to 3 are shown in FIG. Figures 2 to 4 The curve of the differential pore volume of the boron nitride powder obtained in Comparative Example 1 relative to the pore radius is shown in Figure 5 . Based on the obtained differential pore volume curve, the above-mentioned pore radius R1, R2 and R3, differential pore volumes V2 and V3, slopes a and b of the straight line, cumulative pore volume up to a pore radius of 1.2 μm, and cumulative pore volume up to a pore radius of 500 μm were calculated. The results are shown in Table 1. In addition, the bulk density of the boron nitride powder was calculated based on the density of the boron nitride particles (2.26 g / ml) and the cumulative pore volume.
[0085] [Measurement of average particle size of boron nitride powder]
[0086] The average particle size of the boron nitride powder is measured in accordance with ISO13320:2009 using a laser diffraction scattering particle size distribution measuring device (manufactured by Beckman Coulter, Inc., "LS-13320"). The measurement is performed without using a homogenizer on the sample before the measurement process. When measuring the particle size distribution, water is used as a solvent for dispersing the boron nitride powder, and hexametaphosphoric acid is used as a dispersant. At this time, a refractive index of 1.33 is used for water, and a value of 1.7 is used for the refractive index of the boron nitride particles. The measurement results are shown in Table 1.
[0087] [Measurement of BET specific surface area of boron nitride powder]
[0088] The BET specific surface area of the boron nitride powder was measured by a BET multipoint method using nitrogen gas in accordance with JIS Z 8830: 2013. The measurement results are shown in Table 1.
[0089] [Table 1]
[0090]
[0091] [Measurement of thermal conductivity]
[0092] 100 parts by mass of naphthalene epoxy resin (HP4032 manufactured by DIC Corporation) and 10 parts by mass of imidazole compound (2E4MZ-CN manufactured by Shikoku Chemical Industry Co., Ltd.) as a curing agent were mixed, and then the boron nitride powders obtained in Example 1 and Comparative Example 1 were mixed in such a way that the filling rate of the boron nitride powder was 70% by volume to obtain a resin composition. The resin composition was degassed at a reduced pressure of 500 Pa for 10 minutes and applied to a PET sheet in such a way that the thickness became 1.0 mm. Then, the mixture was heated to 150°C and the pressure was 160 kg / cm 2 The heat-pressing was carried out for 60 minutes under the same conditions to produce a 0.5 mm sheet-shaped heat dissipation material. A 10 mm × 10 mm sample for measurement was cut out from the produced heat dissipation material, and the thermal diffusivity A (m 2 In addition, the specific gravity B (kg / m 3 ) was measured. In addition, a differential scanning calorimeter (ThermoPlus Evo DSC8230, manufactured by Rigaku Corporation) was used to measure the specific heat capacity C (J / (kg·K)) of the measurement sample. Using these physical property values, the thermal conductivity H (W / (m·K)) was calculated according to the formula H=A×B×C. The thermal conductivity of the heat dissipation material made using the boron nitride powder obtained in Example 1 is 22W / (m·K), and the thermal conductivity of the heat dissipation material made using the boron nitride powder obtained in Comparative Example 1 is 17W / (m·K).
Claims
1. A boron nitride powder comprising boron nitride particles having fine pores, In a curve of differential pore volume relative to pore radius measured by a mercury porosimeter, when a point where the differential pore volume curve rises and a point where the differential pore volume reaches a maximum value are connected by a straight line within a range where the pore radius is less than 1.2 μm, the slope of the straight line is less than 0.
8.
2. The boron nitride powder according to claim 1, wherein The cumulative pore volume within the range of the pore radius being 1.2 μm or less is 0.2 ml / g or less.
3. The boron nitride powder according to claim 1, wherein The maximum value is below 0.4 ml / g.
4. The boron nitride powder according to claim 1, wherein The maximum value is 0.1 ml / g or more. 5 . A resin composition comprising a resin and the boron nitride powder according to claim 1 .
Citation Information
Patent Citations
Hexagonal boron nitride powder and method for producing the same
JP2016160134A